Netizens' Language Politeness In The 2024 Presidential Debate Comments Column On Youtube Media - Mukhtar, Ruyatul Hilal; Ibrahim, Anwar (UNIVERSITAS PAKUAN, 2024)
This research aims to describe (1) the use of the principles of politeness in language (2) violations of the principles of politeness in language committed by netizens in